Petreni, Republik Moldau - Uhl, Regina (e-Forschungsberichte des DAI, 2023)
The so-called Trypillia megasites, one of the largest Chalcolithic Eurasian sites (5th and 4th millennium BC), give evidence of a socio-economic shift in the northwest-pontic region. Because of the scarcity of consistent chronological data, the function of these settlements is still unknown. The research at Petreni (Republic of Moldova) aims to reconstruct the inner settlement structure in order to define the extent of the settlement at specific points of time and to estimate the approximate number of inhabitants in the settlement Petreni accordingly.